A Sc(OTf)3 catalyzed Mukaiyama–Mannich reaction of difluoroenoxysilanes with unactivated ketimines. Issue 14 (6th June 2019) - Hu, Xiao-Si; Ding, Pei-Gang; Yu, Jin-Sheng; Zhou, Jian
Abstract : The first example of a Mukaiyama–Mannich reaction of difluoroenoxysilanes with unactivated ketimines catalyzed by Sc(OTf)3 is described. Abstract : An efficient Mukaiyama–Mannich reaction of difluoroenoxysilanes with unactivated ketimines enabled by 5 mol% of Sc(OTf)3 is reported here. This protocol provides expedient access to a series of α, α-difluoro-β-amino ketones possessing a tetrasubstituted carbon center in moderate to high yields (up to 89% yield). Moreover, the Mannich adducts could be easily converted into diversified gem -difluorinated compounds.